Impact of Expiratory Strength Training in Amyotrophic Lateral Sclerosis - Plowman, Emily K. (Muscle Nerve, 2016)
INTRODUCTION: We evaluated the feasibility and impact of Expiratory Muscle Strength Training (EMST) on respiratory and bulbar function in persons with amyotrophic lateral sclerosis (ALS). METHODS: 25 ALS patients participated in this delayed intervention open-label clinical trial. Following a lead-in period, patients completed a 5-week EMST protocol. Outcome measures included: maximum expiratory pressure (MEP), physiologic measures of swallow and cough, and Penetration-Aspiration Scale (PAS) scores. RESULTS: Of those participants who entered the active phase of the study (n=15), EMST was well tolerated and led to significant increases in MEPs and maximum hyoid displacement during swallowing post-EMST (P<0.05). No significant differences were observed for PAS scores or cough spirometry measures. DISCUSSION: EMST was feasible and well tolerated in this small cohort of ALS patients and led to improvements in expiratory force-generating pressures and swallow kinematics. Further investigation is warranted to confirm these preliminary findings.